Analysis And Evaluation Of Audio Induced Acoustic Fatigue Using Infrared Imaging - et. al., Tinny Sawhney, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Every system whether living or non-living has a threshold of time for which it can work efficiently. If the system is used beyond its threshold, a fatigue is developed and the efficiency reduces. Any acoustic activity, including continuous listening or speaking also introduces fatigue called acoustic fatigue within the human beings and some time, it is responsible for several problems even not directly related to input audio stimulus. The treatments available for tackling fatigue related problems in the human body may be categorized as chemical compounds balancing, surgical practices, and application of special acoustic vibrations based techniques. The objective of the paper is to investigate the effect of acoustic vibrations in the form of pure tone frequencies on reduction of the fatigue introduced due to some unknown stimuli within the human subjects by using infrared (IR) imaging. In the proposed research, IR images obtained as a result of applying acoustic vibrations have been used for estimating the acoustic fatigue. The images were analyzed with respect to 3D and linear spatial temperature profiles. In most of the cases,the analysis of the temperature profiles of different subjects showedleft side of the brainis activated corresponding to 174Hz pure tone suggesting unpleasant perception (i.e. fatigue) within the subjects for prolonged durations of stimuli. On the other hand, 432Hz activates the right side of the brain indicating relaxed state of mind (lower fatigue). Evaluation of the entropy of the thermal images also reveals the reduction in fatigue due to 174 Hz and 432 Hz tones..